1990
DOI: 10.1111/j.1476-5381.1990.tb12950.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of bradykinin‐induced contraction in canine veins via thromboxane/prostaglandin endoperoxide receptor activation

Abstract: Canine jugular and femoral veins were studied to determine the possible importance of thromboxane (TXA2) and prostaglandin endoperoxides (prostaglandin H2, PGH2) in mediating bradykinin(BK)‐induced contraction. Isolated vein rings incubated in modified Krebs solution contracted to TXA2/PGH2 analogs SQ26655 and U44069 with potency of contraction exceeding that for BK. The potency ranking for both veins was SQ26655 > U44069 > BK > PGF2α > TXB2 > PGD2. The cyclo‐oxygenase inhibitors indomethacin (3 × 10−7 m) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…A number of studies demonstrated that the different cyclooxygenase products of arachidonic acid, such as prostaglandin F 2α (PGF 2α ), prostaglandin H 2 (PGH 2 ), or thromboxane A 2 (TXA 2 ), have been involved in the bradykinin contractile effects in various blood vessels [12, 2327]. Our results were in line with the quoted studies, since cyclooxygenase inhibition completely abolished the bradykinin-produced contraction of the femoral artery.…”
Section: Discussionsupporting
confidence: 91%
“…A number of studies demonstrated that the different cyclooxygenase products of arachidonic acid, such as prostaglandin F 2α (PGF 2α ), prostaglandin H 2 (PGH 2 ), or thromboxane A 2 (TXA 2 ), have been involved in the bradykinin contractile effects in various blood vessels [12, 2327]. Our results were in line with the quoted studies, since cyclooxygenase inhibition completely abolished the bradykinin-produced contraction of the femoral artery.…”
Section: Discussionsupporting
confidence: 91%
“…The bradykinin-induced vasoconstrictor response has been reported to be endothelium-independent and indomethacin-sensitive or mediated by bradykinin B 2 receptors located in the vascular smooth-muscle layer (2,9). In addition, other studies have shown that the action of bradykinin was largely dependent on stimulation of the cyclooxygenase pathway to produce PGH 2 and possibly TXA 2 , which can activate smooth muscle TXA 2 / PGH 2 receptors to elicit vasoconstriction (10,11). However, the bradykinin-induced vasoconstriction in the canine isolated saphenous vein without endothelium was potentiated by indomethacin (26).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this finding strongly suggests that PGH 2 is responsible for the bradykinin-induced endotheliumindependent vasoconstriction in the rat mesenteric artery. Bradykinin has been shown to cause vasoconstriction (10,24,25). The bradykinin-induced vasoconstrictor response has been reported to be endothelium-independent and indomethacin-sensitive or mediated by bradykinin B 2 receptors located in the vascular smooth-muscle layer (2,9).…”
Section: Discussionmentioning
confidence: 99%
“…A különböző AA-metabolitok kisvénákban kifejtett vazoaktív hatásai régió-és fajfüggő különbsége-ket mutattak, például humán vena saphenában a prosztaciklin kontrakciót, míg kézvénákban relaxációt okozott [45]. Továbbá számos vazoaktív anyagról és mechanikai faktorról igazolták, hogy befolyásolják az érfalban tör-ténő prosztaglandinok termelését, ezáltal szabályozva a kisvénák vazomotortónusát [46,47]. Feltételezhető, hogy a különböző lokális humorális és biomechanikai té-nyezők egymás hatását is módosítva, együttesen határoz-zák meg a vascularis endothelialis faktorok termelését és ezáltal szabályozzák a kisvénák tónusát.…”
Section: Az Endothelialis Vazomotormechanizmusok Moduláló Szerepeunclassified